The Practice of Peace Education: Applied Research on Peace Education in the Twenty-First Century - Osias Kit T. Kilag; Odilon C. Mambaje; Amor A. Rabi; Jhonrey C. Uy; Elaine G. Miñoza; John Byron G. Padilla (Journal of Higher Education and Academic Advancement, 2024)
This study explores the practice of peace education in the Philippines in the twenty-first century. Data were collected through interviews and focus group discussions with teachers and students from various schools. Thematic analysis was used to analyze the data, which revealed several key findings. First, the implementation of peace education varies across schools, with some schools prioritizing it more than others. Second, teachers play a crucial role in promoting peace education, particularly those who are passionate about the topic and receive training and support in this area. Third, peace education should be integrated into the formal curriculum and tailored to be age-appropriate and culturally relevant. Fourth, the lack of resources and support is a major challenge in promoting peace education. Fifth, social justice education is an important component of peace education. Lastly, peace education should be promoted at all levels of education, from primary school to university. Overall, the findings highlight the importance of prioritizing peace education and providing resources and support to educators in promoting it. By integrating peace education into the formal curriculum and tailoring it to be age-appropriate and culturally relevant, students can develop positive values and attitudes towards peace and conflict resolution.